(untitled) (World Bulletin of Public Health, 2024)
The number of children born with congenital pathology of the maxillofacial region remains significant. Congenital bilateral cleft lip and palate is the most severe form of facial cleft. Such patients have severe anatomical and functional disorders that require long-term and multi-stage recovery. Currently, the treatment of such patients is carried out comprehensively and includes the participation of a maxillofacial surgeon, speech therapist, otolaryngologist, pediatrician, orthodontist, etc. Throughout the entire period of treatment, orthodontic correction not only improves the functional and aesthetic indicators of the dentofacial system, but is also a preparatory stage to continue treatment with other specialists. At the same time, it is necessary to clarify some details of the method itself and the design features of the device, as well as to develop indications for the use of one or another type of orthodontic treatment, depending on the degree, severity and shape of the existing deformity and the choice of tactics for preparing the patient for primary surgical treatment.